Technological progress and regional disparities in (un)employment - Uwe Blien; Oliver Ludewig (European Regional Science Association (ERSA), 2014)
One of the key issues in economics is the explanation of unemployment and its variation across different economies. Doing so, modern mainstream macroeconomics refers to the effects of financial crises and to institutional structures and their variation across countries. However, unemployment within the European states varies nearly as much as between these countries. In the interior of a country, however, there are only minor differences in institutions. Therefore, the large variation in regional unemployment and in the development of employment is puzzling. Our explanation of this regional variation of unemployment builds on the regional industry composition and technological progress. It is shown formally that under very general and standard preconditions the elasticity of demand on product markets is decisive: Technological progress leads to an expansion of employment if product demand is elastic. It is accompanied, however, by shrinkage of employment if product demand is inelastic. A transition from the elastic into the inelastic range of the demand function for the most important product(s) can already suffice to plunge a region into crisis. In our empirical analysis we use industry level time series data on output, prices, employment and national income for Germany provided by the Federal Statistical Office and the OECD. We estimate Marshallian type demand functions using an instrumental variables estimator to derive the price elasticities for different industries and link this information to the regional labour market performance of the respective industries and regions.
Keywords: Q33; R11; J23; 330